The Influence of Digital Literacy and Income on the Consumptive Behavior of Generation Z in Gowa Regency with E-Commerce Usage as a Moderating Variable - Rijal, Syamsu; Tadampali, Andi Caezar To; Mutmainna, A. Indah; Arisah, Nur; S, Ratnah (International Journal of Business, Law, and Education, 2025)
This study aims to gain knowledge and understanding of the influence of digital literacy and income on the consumptive behavior of Generation Z in Gowa Regency, with e-commerce usage as a moderating variable. The method used in this research is quantitative research with a descriptive research type. The sample in this study consists of 100 respondents. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) model. The results show that digital literacy significantly influences consumptive behavior. Income significantly influences consumptive behavior. Digital literacy significantly influences e-commerce usage. Income significantly influences e-commerce usage. E-commerce usage significantly influences consumptive behavior. E-commerce usage is able to moderate the relationship between digital literacy and consumptive behavior. However, e-commerce usage does not moderate the relationship between income and consumptive behavior.